2020
DOI: 10.5505/amj.2020.71542
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of Thiol Disulphide Homeostasis And Neutrophile Lymphocyte Ratio In Carbon Monoxide Intoxication:

Abstract: Bu çalışmanın amacı acil servise karbon monoksit zehirlenmesi nedeniyle başvuran hastalarda oksidatif stres markerlarından olan thiol/disülfit homeostazis parametreleri ile Nötrofil-Lenfosit (NLO) beraber kullanımının tanı açısından yararlı olup olmadığını araştırmaktır. Materyal ve Metot: Çalışma 01.01.2014 ile 01.03.2015 tarihleri arasında acil servise başvuran ve çalışmaya alınan 45 hasta ve kontrol grubu olarak belirlenen 40 sağlıklı kişi ile prospektif olarak yapıldı. Erel ve Neşelioğlu tarafından yeni ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The degree of NLR reduction can aid in determining clinical severity. 40,41 Moon et al found that over the first 12 hours after admission, patients with poor long-term neurological outcome had higher NEU, MON, and NLR levels as well as lower LYM counts than patients with a good outcome. 42 In our study, we found a statistically significant increase in NEUs, WBCs, LYMs, and NLR in COP patients compared with the control group and in the severe poisoning group compared with the mild poisoning group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The degree of NLR reduction can aid in determining clinical severity. 40,41 Moon et al found that over the first 12 hours after admission, patients with poor long-term neurological outcome had higher NEU, MON, and NLR levels as well as lower LYM counts than patients with a good outcome. 42 In our study, we found a statistically significant increase in NEUs, WBCs, LYMs, and NLR in COP patients compared with the control group and in the severe poisoning group compared with the mild poisoning group.…”
Section: Discussionmentioning
confidence: 99%
“…Although the number of leukocytes remains constant, a decrease in NEUs and an increase in LYMs can result in a significant decrease in NLR levels. The degree of NLR reduction can aid in determining clinical severity 40,41 . Moon et al found that over the first 12 hours after admission, patients with poor long-term neurological outcome had higher NEU, MON, and NLR levels as well as lower LYM counts than patients with a good outcome 42 .…”
Section: Discussionmentioning
confidence: 99%